2016
DOI: 10.1590/2317-4889201620150010
|View full text |Cite
|
Sign up to set email alerts
|

Lead isotope constraints on the mantle sources involved in the genesis of Mesozoic high-Ti tholeiite dykes (Urubici type) from the São Francisco Craton (Southern Espinhaço, Brazil)

Abstract: ABSTRACT:The first results of Pb isotope compositions of the high-Ti Mesozoic dykes of the Southern Espinhaço are presented. The results do not show large variations and are significantly more radiogenic than the Pb isotope compositions of the high-Ti tholeiites from the Paraná Continental Flood Basalts. The data combined with published geochemical and Sr-Nd isotope results rule out crustal contamination processes in the genesis of the dykes, requiring magma generation in metasomatized subcontinental lithosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…and occur in the northern and southern PCMP, respectively. Recent studies have shown that some Urubici flows are present in the border region between Minas Gerais and São Paulo states (Machado 2005), as well as dikes crosscutting rocks of the São Francisco Craton, Minas Gerais (Seer et al 2011, Marques et al 2016. The age of the main phase of the volcanic activity is concentrated at 134 to 132 Ma, according with data obtained by Renne et al (1992), Thiede and Vasconcelos (2010), and Janasi et al (2011).…”
mentioning
confidence: 74%
“…and occur in the northern and southern PCMP, respectively. Recent studies have shown that some Urubici flows are present in the border region between Minas Gerais and São Paulo states (Machado 2005), as well as dikes crosscutting rocks of the São Francisco Craton, Minas Gerais (Seer et al 2011, Marques et al 2016. The age of the main phase of the volcanic activity is concentrated at 134 to 132 Ma, according with data obtained by Renne et al (1992), Thiede and Vasconcelos (2010), and Janasi et al (2011).…”
mentioning
confidence: 74%
“…1). The Southern Paraná Magmatic Province hosts the Urubici rocks (HTi) (Piccirillo & Melfi 1988, Peate 1997, although some scarce flows (Machado et al 2007) and dykes (Seer et al 2011, Marques et al 2016 are found in the northern area.…”
Section: Geological Contextmentioning
confidence: 99%
“…The composition of the subcontinental lithospheric mantle (SCLM) beneath igneous provinces is closely related to the chemical and isotopic signatures inherited by magmas and related mineral deposits (e.g., Marques et al 2016;Holwell et al 2019;Hutchison et al 2021). The igneous provinces in Brazil include one of the largest mafic-potassic provinces in the world (Alto Paranaíba Igneous Province, APIP), with the presence of mantle xenoliths enclosed in ultramafic rocks brought up by rapid ascension magmas (e.g., kimberlites, kamafugites).…”
Section: Introductionmentioning
confidence: 99%